Pengaruh Desain Produk terhadap Keputusan Pembelian dan Dampaknya pada Kepuasan Konsumen - Jasella Handayani; Derriawan Derriawan; Tyahya Whisnu Hendratni (Journal of Business & Banking, 2020)
Service and tourism companies are increasingly providing applications, one of which is Traveloka to maintain and gain a higher market share. To affect the intention to use an application,  a company needs to take a concern about the ease of the operartion, transac-tion security, providing an attractive promo, and also giving a good experience to users. The purpose of this study is to identify factors that influence the intention to use and actual usage such as perceived ease of use, perceived value, perceived usefulness, subjec-tive norms, perceived trust, and image. The data were collected by a quesationnaire to 300 respondents who used the Traveloka application for the past year using a Simple Random Sampling method. The data were analysed using Structural Equation Model-ling-Partial Least Square (SEM-PLS). The result indicates that perceived ease of use and perceived value do not affect the intention to use but perceived usefulness, subjective norms and perceived trust are affecting the intention to use. The intention to use also affect actual usage and image also affect actual usage.